Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

if f(1)=3 and f(n)=-2f(n-1), then f(5)=

Sagot :

AyaZ
[tex]f(n)=-2 f_{n-1} \\ f_{1} =3 \\ f(2)=-2 f_{1}=-2*(3)=-6 \\ f(3)=-2 f_{2}=-2*(-6)=12 \\ f(4)=-2 f_{3}=-2*(12)=-24 \\ f(5)=-2 f_{4}=-2*(-24)=48[/tex]

and

[tex] f_{n} =3* (-2)^{n-1} [/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.